2020
DOI: 10.5194/amt-2020-28
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric observations with E-band microwave links – challenges and opportunities

Abstract: Opportunistic sensing of rainfall and water vapor using commercial microwave links operated within cellular networks was conceived more than a decade ago. It has since been further investigated in numerous studies predominantly 10 concentrating on the frequency region of 15-40 GHz. This manuscript provides the first evaluation of rainfall and water vapor sensing with microwave links operating at an E-band (specifically, 71-76 GHz and 81-86 GHz), which are increasingly updating, and frequently replacing, older … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…The return of baseline attenuation to previous dry-weather levels is attributed to the drying of the antenna radomes(Van Leth et al, 2018). The same behaviour was observed by new E-bands and reported recently inFencl et al (2020).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The return of baseline attenuation to previous dry-weather levels is attributed to the drying of the antenna radomes(Van Leth et al, 2018). The same behaviour was observed by new E-bands and reported recently inFencl et al (2020).…”
supporting
confidence: 91%
“…Although, to date, most CMLs use frequencies from 5 GHz to 40 GHz, the spectrum is currently further extended to 80 GHz. Recently, Fencl et al (2020) used PARSIVEL observations from the CoMMon dataset to simulate rainfall retrieval from an E-band CML which demonstrated that these may be promising tools for sensing light rainfall which is challenging for lower frequencies due to the quantization of the attenuation data (Berne and Schleiss, 2009). In a similar fashion, CMLs are "blind" regarding extremely high intensities as attenuation due to such high intensities drops below the receiver threshold of the hardware and causes outages of the CML (cf.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, convolutional neural networks (CNNs) are considered one of the leading neural network architectures for image and time series classification. CNNs are inspired by the visual cortex of mammals, and they are designed to recognize objects or patterns, regardless of their location in images or time series (Fukushima, 1980). They are characterized by local connections of neurons, shared weights, and a large number of layers of neurons, involving pooling layers (LeCun et al, 2015).…”
Section: Data-driven Optimization Through Deep Learningmentioning
confidence: 99%
“…Recent acquisition method developments by Chwala et al (2016) and the project TEL4RAIN (2020) are promising in this direction. Moreover, the introduction of 5G cellular networks can lead to new opportunities as E‐band CMLs are an essential part of these networks (Ericsson, 2019; Fencl et al, 2020). Provided that the nowcasts are skillful on the relevant spatial resolutions and lead times, CML nowcasts can provide an opportunity to reduce fatalities and economic loss, e.g., by improving hazardous weather and (flash‐)flood early warning(s).…”
Section: Discussionmentioning
confidence: 99%